Anemia Prevalence and Iron Supplementation Practices Among Pregnant Women in Vancouver, Canada. (7th June 2021) - Cochrane, Kelsey; Elango, Rajavel; Devlin, Angela; Hutcheon, Jennifer; Karakochuk, Crystal
Abstract: Objectives: Health Canada recommends supplementation with 16–20 mg iron during pregnancy to maintain adequate iron stores and reduce the prevalence of iron deficiency. Most prenatal vitamins contain 27 mg iron (the recommended dietary allowance). In the case of diagnosed iron deficiency (typically defined as a ferritin concentration < 15–50 µg/L), some pregnant women may be recommended to take additional iron. Iron is an essential nutrient and adequate intake is needed for a healthy pregnancy; however, excess iron can also be harmful. We aimed to evaluate the hematological profile, prevalence of anemia, and iron supplementation practices of healthy pregnant women in Vancouver, Canada. Methods: As part of an ongoing clinical trial, 40 healthy pregnant women (aged 19–42 years) received prenatal vitamins containing 27 mg iron over 16 weeks of pregnancy, starting at 9–21 weeks gestation. A complete blood count was measured at baseline and endline. Anemia was defined as hemoglobin < 110 g/L in the first/third trimesters and < 105 g/L in the second trimester. Microcytic anemia (most commonly caused by iron deficiency) was defined as having both anemia and a MCV concentration < 80 fL. Participants reported other supplement use throughout the study, including additional iron prescribed for treatment of iron deficiency and/or anemia. Results: At baseline and endline, the mean ± SD of hemoglobin was 124 ± 9 g/L and 127 ± 11 g/L; and for MCV was 89 ± 3 fL and 91 ± 3 fL, respectively. Based on hemoglobin (trimester-specific) and MCV thresholds, no participants were classified as having anemia or microcytic anemia at either timepoint, respectively. At endline, a total of n = 8 women (20%) reported that following their baseline visit (during the intervention period) they were informed by their health care provider to increase their supplemental dose of iron up to 300 mg, in addition to the 27 mg in the study prenatal vitamin. Conclusions: Whether recommendation for additional iron was warranted in 20% of women is unclear, as none had microcytic anemia based on hemoglobin and MCV values. Measurement of ferritin is warranted for the definitive diagnosis of iron deficiency, and to elucidate if there is a need for improved clinical practices for recommending additional iron supplementation. Funding Sources: Healthy Starts Catalyst Grant (BC Children's Hospital Research Institute, Vancouver, Canada).